Pemodelan Perubahan Banjir di Pamenang Barat Menggunakan HECRAS - Andarino, Bastian (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2021)
Flood is one of the most frequent hydrological disasters in Jambi province. The impact caused by the flood disaster can affect various sectors and cause material losses to fatalities. During the period 2010 to 2019 there have been 149 floods with the area experiencing the most damage, namely the West Pamenang sub-district. West Pamenang District is located in the Batanghari Watershed (DAS) precisely in the Batang Merangin Tembesi sub-watershed. Flood risk analysis can be done by modelling. One application that can be used is HECRAS with debit data input and DEMNAS. One of the outputs of this application is the flood area. The flood area obtained can be used to determine the impact on the physical area of an area, namely by overlaying it with administrative map data. In addition to flood modelling, analysis of daily rainfall trends, monthly rainfall and rainy days is also carried out to determine rainfall changes. The results of the analysis show that there are changes in the trend of daily rainfall, monthly rainfall and rainy days for five rain posts around the West Pamenang sub-district. In addition, daily rainfall is also related to the maximum river discharge. The increase in the maximum river discharge also results in an increase in the flood area which also makes the resulting impact wider.